IMPLEMENTASI METODE VECTOR AUTOREGRESSIVE DALAM PERAMALAN JUMLAH PRODUKSI PADI DI KABUPATEN BADUNG - Margaretha Ratih Dyah Novitasari; I Wayan Sumarjaya; I Gusti Ayu Made Srinadi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Forecast is a process to predict something in the future using past data. One of common model used in forecast is time series data that is vector autoregressive (VAR) model. The research purpose is to know the model and amount of rice production in Badung regency. It is used seconder data get from the BPS office Bali and BMKG Denpasar, that are rice production data, harvest area, and rainfall from Januari 2018 till December 2022. Base on lag optimum model VAR, the research result show that the VAR(1) model is suitable being used. Therefore, base on MAPE forecast criteria the VAR model in this research show the result less accurate. Eventhough the forecast pattern for rice production, harvest area, and rainfall show the stability. Beside that in the first period there is shocking in the IRF analysis but finally reach the stabil condition. Keywords: Forecast, VAR models, Rice Production, Harvest Area, Rainfall